Optimizing sowing date for enhanced heat stress tolerance in canola (Brassica napus L.): Investigating impacts on seed yield, oil content, and fatty acids composition - Seyed Ahmad Kalantar Ahmadi; Mohsen Sarhangi (Heliyon)
Environmental conditions, including temperature and the occurrence of phenological stages at the optimum temperature, are effective factors on seed yield, oil content and fatty acids. An experiment was carried out as strip block based on randomized completed block design with three replications in Safiabad Agricultural and Natural Resources Research and Education Center of Dezful during two cropping seasons (2017–2019). Vertical factors consisted of six levels of sowing date (23 Sep, Oct 7, 22 Oct, Nov 6, 21 Nov, Dec 6), and horizontal factors were seven genotypes (Agamx, Hyola4815, Hyola50, Hyola401, Safi6, Zabol9 and Zabol13). Elevated temperatures resulting from postponed sowing dates during the silique formation and seed filling phases led to a decline in seed yield, oil content, and modifications in the fatty acid composition of the studied canola genotypes. The highest (43.04 %) and lowest (38.81 %) oil content over the two years of testing were attributed to the genotypes Hyola50 and Hyola4815, respectively. Postponing the sowing date contributed to a higher accumulation of oleic acid in the examined genotypes. The maximum oleic acid content (62.14 %) was observed on Dec. 6 for the genotype Hyola50, while the minimum oleic acid content (50 %) was recorded on Sep. 23 for the genotype Zabol9 during two years of the experiment. Variations in climatic conditions across the two experimental years elicited distinct responses in the studied genotypes based on the sowing date. In the first year, Agamax genotype produced the highest seed yield (3357 kg ha−1) on Oct 7th, but in the second year the highest seed yield (2888.9 kg ha−1) belonged to the second sowing date (Oct. 7) and Hyola50 genotype. Based on the test results, the susceptibility of canola genotypes to temperature, rainfall, and lodging during seed filling period varied between the two years of the experiment. The percentage reduction in seed yield for the Hyola50 and Agamax genotypes was 32 % and 40 %, respectively. Climatic factors, particularly temperature and the synchronization of phenological stages with optimal thermal conditions, play a crucial role in determining seed yield, oil content, and fatty acid composition. Furthermore, the selection of heat-tolerant genotypes is essential for maintaining yield stability.